Interdialytic Exercise Reduces Fatigue in Chronic Kidney Failure Patients: Systematic Literature Review - Wayunah Wayunah; Wiwin Nur Aeni; Aulia Faturrohman; Muhammad Saefulloh (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Hemodialysis therapy that is carried out for a long time can cause physical stress in the form of fatigue and have an impact on the patient’s quality of life. Giving intradialytic exercise intervention is believed to reduce the level of fatigue. The purpose of this study was to determine the effect of intradialytic exercise on the level of fatigue in chronic kidney failure patients undergoing hemodialysis. This study used a systematic literature review method based on data from Google Schoolar, Garuda, Science Direct, and the Directory of Open Access Journal (DOAJ), by including key words are fatigue, chronic kidney failure, hemodialysisi, and intradialytic exercise. Article were selected through screening according to inclusion criteria, including publications within the last 10 years (2011 – 2022), original articles, Indonesian and English, descriptive analytic study types, and quasi experiments. The results show that Intradialytic exercises applied include breathing exercise, Range of Motion (ROM), slow deep breathing, Progressive Muscle Relaxation (PMR), Pursed Lip Breathing and Physical Exercise. Based on the 9 articles found that intradialytic exercise has an effect on the level of fatigue. The average p-value <0.05, the average post-test fatigue score is smaller than the pre=test, the smaller the average value fatigue score then the level of fatigue decreases. In conclusion, Intradialytic exercise affects the fatigue level of chronic kidney failure patients undergoing hemodialysis. Suggestions are given to HD nurses to be able to implement an intradialytic exercise intervention in patients undergoing hemodialysis to reduce fatigue.